The Recovery Effect of Cold Water Immersion and Massage on the Physical Performance of Young Male Soccer Players - Babak Mostafa Farkhani; Mahdi Javadikia; Keyvan Hejazi; Mehrdad Fathi; Seyed Reza Attarzadeh Hoseini; Mohammad Mosaferi Ziaaldini (Islamic Azad University, 2016)
Introduction: In recent years, reducing the time intercept between competitions and increasing the level and number of competitions, has made it one of the trainers' major concerns to adopt and employ a suitable recovery method to reduce fatigue and improve performance. The purpose of this study was to compare the effect of two recovery protocols of cold water immersion and massage on the performance of young male soccer players following an exhaustive exercise session. Methods: Thirty young male soccer players were selected as statistical samples and divided into 3 groups of 10, including cold water immersion (CWI), massage (M) and passive recovery (P). 24 hours before and after an exhaustive test of simulated soccer match (90 minutes), tests of 20 m sprint, 40 m sprint, agility, vertical jump and RSA were taken from the subjects. To analyze the findings, dependent t-test, one-way ANOVA and Tukey's post hoc test were used (p≥0.05). Results: There was no significant difference in the rate of variation in 20 m sprint and Sargent jump performances in the subjects of three groups (P≤0.05). Also, the agility of the CWI recovery group was significantly improved compared to the massage recovery group (P = 0.003). However, the repeat sprints ability in the recovery group of massage was significantly improved compared to the CWI recovery group (p = 0.01). Conclusion: Using both recovery methods of cold water immersion and massage after an exhaustive exercise session has a positive effect on the performance of young male soccer players, and if the conditions are met, then both recovery methods will probably have positive effects.